Affective solidarity and mediated distant suffering: In defence of mere feltness. (July 2019) - Markham, Tim
In recent media and political theory the idea of affective solidarity has been treated as a contradiction in terms. Any relation to the other consisting in sympathy or pity cannot form the basis of full subjective recognition of the other, and in practice is often actively dehumanising. Further, there remains the notion that solidarity is contingent upon a rupture of habitual being in the world that produces a revelatory consciousness of the subjectivity of the other. In journalistic contexts this leads to practices that aim at intensive or extensive encounters that transcend the affective livedness of everyday routines. Against these conventional wisdoms, this article argues that solidarity with distant others is not clinched in spite of the merely felt experience of the other in everyday life – an experience characterised by distraction, ambivalence and unreflexive sentimentality – but instead is predicated precisely on that mere feltness. Drawing on Heidegger's notion of findingness, Withy's disclosive postures and Levinas's ascription of ethics to the fundamental priority of coexistence, it is proposed that feeling the right way about distant suffering may be immaterial. In practical terms, it concludes with a call to shift our empirical focus away from the question of how media can produce meaningfully solidaristic encounters between distant others, to ask instead what kinds of ordinary mediated affect already existing in the world might afford solidarity.